PEMANFAATAN TANAMAN LOKAL SEBAGAI PELANCAR ASI (GALAKTOGOGUE) - Sri Handayani; Yopi Suryatim Pratiwi; Nurul Fatmawati (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: Poor nutritional status is the cause of pneumonia and diarrhea in infants and toddlers. This incidence can be reduced through exclusive breastfeeding. The achievement of exclusive breastfeeding in Indonesia is still far from the national target, one of which is caused by the lack of breast milk production. In Indonesia, there are many plants that can promote breast milk, including katuk leaves, moringa leaves, young papaya fruit, wake-up, and fenugreek. The use of local plants as a breast milk facilitator must be supported by comprehensive information regarding the dosage form, dosage and duration of use, empirical benefits, and possible side effects.Objective: The aim of the study was to describe the use of local plants as breast milk carriers (galactogogue). Method: The method in this research is quantitative. This research was conducted in Terong Tawah Village, Labuapi District, West Lombok Regency in April 2021. The sample in this study were all mothers who had babies aged 0-2 years, as many as 123 people. The instrument in this study used a questionnaire made on google form. The research was conducted by sending a questionnaire via WhatsApp message. The data obtained were analyzed by univariate. Results: The results showed that the plants used to facilitate breastfeeding by the community were katuk leaves, moringa leaves, turi leaves, and spinach. These plants are processed by clear vegetable.Conclusion: Plants used by the community are scientifically proven to increase breast milk production. Further research needs to be done, one of which is about processing clear vegetables.Suggestion there is a need for further research on how to process clear vegetables so that they have the maximum effect. Keywords: Breast milk, Galaktogogue, Clear Vegetable, Plants. ABSTRAK Latar belakang: Status gizi kurang merupakan penyebab kejadian pneumonia dan diare pada bayi dan Balita.  Kejadian ini dapat diturunkan melalui pemberian ASI eksklusif. Capaian ASI eksklusif di Indonesia masih jauh dari target nasional, salah satunya disebabkan oleh produksi ASI kurang. Di Indonesia terdapat banyak tanaman yang dapat melancarkan ASI, diantaranya daun katuk, daun kelor, buah papaya muda, bangun-bangun, dan klabet. Penggunaan tanaman lokal sebagai pelancar ASI harus didukung informasi yang komprehensif terkait bentuk sediaan, dosis, lama penggunaan, manfaat empiris, dan kemungkinan efek samping.Tujuan: Penelitian bertujuan untuk mengetahui gambaran pemanfaatan tanaman lokal sebagai pelancar ASI (galaktogogue).Metode: Metode dalam penelitian ini adalah kuantitatif. Penelitian ini dilaksanakan di Desa Terong Tawah, Kecamatan Labuapi, Kabupaten Lombok Barat pada bulan April  2021. Sampel dalam penelitian ini adalah semua ibu yang memiliki bayi usia 0-2 tahun, yaitu sebanyak 123 orang. Instrumen dalam penelitian ini menggunakan kuesioner yang dibuat pada google form. Penelitian dilakukan dengan mengirimkan kuesioner melalui pesan whatsApp. Data  yang diperoleh dianalisis secara univariat .Hasil: Hasil penelitian menunjukkan tanaman yang dimanfaatkan untuk memperlancar ASI oleh masyarakat adalah daun katuk, daun kelor, daun turi,dan bayam.  Tanaman tersebut diolah dengan cara disayur bening.Kesimpulan: Tanaman yang digunakan masyarakat terbukti dapat memperlancar ASI.Saran perlu adanya penelitian lanjutan, salah satunya tentang cara pengolahan sayur bening sehingga menimbulkan efek maksimal. Kata Kunci: ASI, Galaktogogue, Sayur Bening,Tanaman.